The Effect of Audit Tenure, Audit Committee, Audit Rotation, and Audit Fee on Audit Quality Based on the Literature Review of Two Journals Indexed by Sinta in 2021 and 2023 - Marpaung, Wilson (Program Studi Magister Akuntansi, Direktorat Pascasarjana, Universitas Sangga Buana, 2025)
This study explores the impact of key variables namely audit tenure, the presence of audit committees, audit rotation, and audit fees on the quality of audits. Utilizing a descriptive method with a qualitative lens, the analysis draws upon findings from two Sinta-indexed journals published in 2021 and 2023. The review reveals that prolonged audit tenure may negatively affect audit quality, while the role of an active audit committee appears to enhance it. Interestingly, divergent perspectives emerge between the two journals concerning audit rotation and audit fees. One journal suggests that audit rotation does not significantly influence audit quality, whereas the other indicates a detrimental effect. Similarly, while one source argues that higher audit fees could potentially improve audit quality, the other finds no meaningful relationship between audit fee levels and audit quality. These contrasting interpretations highlight the nuanced and sometimes conflicting views within academic literature. Overall, the study offers critical reflections for auditors, scholars, and regulatory bodies seeking to better understand the multifaceted nature of factors shaping audit quality.